REASONS AND TREATMENT FOR URETERAL AVULSION - B. K. Komyakov; B. G. Guliev; S. N. Idrisov; A. S. Shipilov (Вестник урологии)
Abstract. From 2010 to 2016 years we obsreved 8 patients with ureteral avulsion after endoscopic surgeries. All patients were men, their age ranged from 50 to 71 years. In all patients the ureter was damaged during ureteroscopy with lithotripsy and lithoextraction. Of the 8 patients, two  had proximal ureteral avulsion between upper and middle thirds, four had ureteral avulsion 4 cm away from the pyeloureteral junction , two had had complete pyeloureteral junction avulsion. In 7 cases trauma of ureter occured at other hospitals. These patients were underwent revision of retroperitoneal space and drain for kidney by nephrostomy (6) and ureterocutaneostomy (1). One case occurred at our department and this patient was underwent laparoscopic nephrectomy with autotransplantation. The patient with ureterocutaneostomy was treated by nephrovesical bypass. In 6 patients with extended ureteral strictures we performed ileoureteroplasty. Results of reconstructive surgeries and nephrovesical bypass were successful in all patients. No intra- and postoperative complications. Mean operative time during uleoureteroplasty was 180 min, laparoscopic nephrectomy with autotransplantation – 210 min, nephrovesical bypass – 110 min. Ureteral avulsion often associated with ureterosopy in patients with large impacted proximal ureteral stones. In most cases after these injuries were diagnosed extended ureteral stricture that requires performing for autotransplantation or ileoureteroplasty.